Automated Solution-Phase Synthesis of Insect Glycans to Probe the Binding Affinity of Pea Enation Mosaic Virus - Tang, Shu-Lun (J Org Chem, 2015)
[Image: see text] Pea enation mosaic virus (PEMV)—a plant RNA virus transmitted exclusively by aphids—causes disease in multiple food crops. However, the aphid-virus interactions required for disease transmission are poorly understood. For virus transmission, PEMV binds to a heavily glycosylated receptor aminopeptidase N in the pea aphid gut and is transcytosed across the gut epithelium into the aphid body cavity prior to release in saliva as the aphid feeds. To investigate the role of glycans in PEMV–aphid interactions and explore the possibility of viral control through blocking a glycan interaction, we synthesized insect N-glycan terminal trimannosides by automated solution-phase synthesis. The route features a mannose building block with C-5 ester enforcing a β-linkage, which also provides a site for subsequent chain extension. The resulting insect N-glycan terminal trimannosides with fluorous tags were used in a fluorous microarray to analyze binding with fluorescein isothiocyanate-labeled PEMV; however, no specific binding between the insect glycan and PEMV was detected. To confirm these microarray results, we removed the fluorous tag from the trimannosides for isothermal titration calorimetry studies with unlabeled PEMV. The ITC studies confirmed the microarray results and suggested that this particular glycan–PEMV interaction is not involved in virus uptake and transport through the aphid.